THE EFFECT OF EXERCISE ROPE JUMP AND FRONT CONE HOPS WITH RATIO 1: 1, 1: 2 TO POWER, LIMBS MOTOR STRENGTH, AND VO2 MAX CAPACITY - Mohamad Da'i (Widyagogik, 2022)
Plyometric exercise is a form of training that is quite diverse. In this study the researchers only use two forms of training that is Front Cone Hops and Rope Jump with a ratio of 1:1 and 1:2. By using the ratio 1:1 and 1:2 then this form of exercise in addition to increasing leg muscle strength, leg muscle power can also affect the increase in aerobic capacity. Pre test is done to know the initial data which will be used for division of group in Rope Jump and Front Cone Hops with ratio 1: 1.1: 2. given treatments 3 meetings in 1 week for 6 weeks. A week after the treatments were done post test in all groups. The results of paired t-test after post test in four groups showed significant results for leg muscle strength variables, to increase leg muscle power significantly only occurred in Front Cone Hops 1: 1 training group, and Front Cone Hops 1: 2. However, for aerobic capacity improvement showed less significant results in the four training groups. So it can be concluded that plyometric exercise using Front Cone Hops and Rope Jump with a ratio of 1: 1 and 1: 2. very efficient to increase leg muscle strength and leg muscle power but less efficient to increase aerobic capacity.